Produção de biossurfactantes a partir da microalga spirulina platensis e seu uso em biorremediação - Schmitz, Roberta (2013)
The biomass production and lipids accumulation of in microalgae have been the focus of many studies in recent years, in view of their potential for application in the environmental area. The lipids may present biosurfactant activity, which also present applications in the most different sectors. The aim of this work was to evaluate the production of microalgal lipids and characterize their surfactant activity . The strains Spirulina platensis LEB -52 and Spirulina platensis Paracas were used. The cultivation conditions that allowed the production of biomass and the accumulation of lipids in microalgae were studied through submerged bioprocess, being the variables studied the addition of glucose, glycerol and iron, in fed-batch mode. The lipids were used to the determination of oil in water (OW) and water in oil (WO) emulsifying activity (EA). After, the microalgal lipids were used in a bioremediation process of a soil contaminated with 4,0% of diesel and biodiesel. The microalgal biosurfactant was added in the quantity of 0.5% in order to characterize this environmental application. The results showed maximum cellular concentration (Cmax) of 5,70g/L to the strain Paracas and 3.82 g/L for the strain LEB-52. The percentage of lipids obtained was 9.51% in the experiment made with the addition of iron and glycerol to strain Paracas, and 6.87% in the experiment accomplished with the addition of all inductors to strain LEB-52, which represents increments of 39.5 % and 84.91 % respectively, in the lipid profile of each strain of microalgae. In relation to OW and WO emulsifiers activities , high activities were obtained for both strains: EAWO of 2.78 UE/mglipids in the test with the addition of all inducers for the strain Paracas, and 4.93 UE/mglipids in the experiment added of iron and glycerol to strain LEB-52; EAWO of 71.64 UE/mglipids was obtained in the experiment added of all inductors to strain Paracas, and 187.76 UE/mglipids in assay added of iron and glycerol to strain LEB-52.The microalgal lipids demonstrated their potential application in bioremediation of diesel and biodiesel, being obtained 81.9 % and 81.7 % of biodegradation for biodiesel and diesel respectively, in tests performed with addition of lipids in microalgal 60 d test. The CO2 evolution test, which represents the microbial activity in the soil, showed elevated C (mg) accumulated in the experiments added of biosurfactant, with 1,341.65 mg and 775.3 mg of C for the soils contaminated with biodiesel and diesel, respectively